ALD assisted nanoplasmonic slot waveguide for on-chip enhanced Raman spectroscopy - Ali Raza; Stéphane Clemmen; Pieter Wuytens; Muhammad Muneeb; Michiel Van Daele; Jolien Dendooven; Christophe Detavernier; Andre Skirtach; Roel Baets (APL Photonics, 2018)
Surface enhanced Raman spectroscopy (SERS) is a widely known sensing technique that uses a plasmonic enhancement to probe analytes in ultra-small volumes. Recently, the integration of plasmonic structures with photonic integrated waveguides promised the full integration of a SERS system on a chip. Unfortunately, the previously reported sensors provide modest overall SERS enhancement resulting in a limited signal to noise ratio. Here, we report a photonic waveguide interfaced SERS sensor that shows an order of magnitude higher pump to Stokes conversion efficiency and lower background than previous realizations. Moreover, the plasmonic structure is fabricated without the use of e-beam lithography but rather using a combination of atomic layer deposition and deep UV photolithography. We investigate numerically the performance of the sensor in terms of Raman conversion efficiency for various design parameters. The experimental results are presented via the acquisition of SERS spectra that show a conversion efficiency of 10−9 for a monolayer of 4-nitrothiophenol. To explore the broadband characteristic of our sensor in the therapeutic spectral window, two different pump wavelengths, i.e., 632 and 785 nm, are used. To the best of our knowledge, this is the first ever broadband SERS demonstration of an on-chip Raman sensor. We further study the reproducibility of our SERS sensor, reaching a relative standard deviation of the acquired spectra (RSD) < 5%.